2021
DOI: 10.1002/tox.23384
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A induced apoptosis via oxidative stress generation involved Nrf2/HO‐1 pathway and mitochondrial dependent pathways in human retinal pigment epithelium (ARPE‐19) cells

Abstract: Bisphenol A (BPA) is an estrogen‐like compound, and an environmental hormone, that is commonly used in daily life. Therefore, it may enter the human body through food or direct contact, causing BPA residues in blood and urine. Because most studies focused on the analysis of BPA in reproductive cells or tissues, regarding evidence the effect of BPA on human retinal pigment epithelium (ARPE‐19) cells unavailable. Accordingly, the present study explored the cytotoxicity of BPA on ARPE‐19 cells. After BPA treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 43 publications
(48 reference statements)
1
19
0
Order By: Relevance
“…Based on the aforementioned data, our results revealed that BPA or γ-irradiation concomitant with oxidative stress and neuroinflammation, there is a remarkable suppression in the gene expression of both Nrf2 and HO-1. These results work in with that of Chiang et al ( 2022 ) who observed downregulation of the Nrf2 and HO-1 gene transcription upon intoxication with BPA. Moreover, Zhang et al ( 2021 ) demonstrated that irradiation impedes the protein and gene expression of the Nrf2 and HO-1 via ROS the main mediators of radiation-induced damage, therefore, inducing cell apoptosis and stimulating numerous inflammatory factors.…”
Section: Discussionsupporting
confidence: 89%
“…Based on the aforementioned data, our results revealed that BPA or γ-irradiation concomitant with oxidative stress and neuroinflammation, there is a remarkable suppression in the gene expression of both Nrf2 and HO-1. These results work in with that of Chiang et al ( 2022 ) who observed downregulation of the Nrf2 and HO-1 gene transcription upon intoxication with BPA. Moreover, Zhang et al ( 2021 ) demonstrated that irradiation impedes the protein and gene expression of the Nrf2 and HO-1 via ROS the main mediators of radiation-induced damage, therefore, inducing cell apoptosis and stimulating numerous inflammatory factors.…”
Section: Discussionsupporting
confidence: 89%
“…Macrophages play a crucial role in the immune system response against toxins and invasive pathogens, such as viruses, microbes, and toxics [ 24 , 25 , 26 ]. Overactivation of macrophages in the human body leads to the production of proinflammatory and lethal mediators, including cytokines, proteases, free radicals, and ROS [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protein related densities were measured and quantified by Infinity CX5 detection system (Vilber Lourmat, France). 22,23…”
Section: Western Blot Assaymentioning
confidence: 99%